OPTIMALISASI EKSTRAKSI PEKTIN DARI KULIT BUAH NAGA MERAH (Hylocereus polyrhizus) MENGGUNAKAN MICROWAVE ASSISTED EXTRACTION: KARAKTERISTIK FISIKOKIMIA DAN APLIKASI EDIBLE FILM - Maha Dewi, Syifa Mentari; Natalia, Tari; Wulandari, Tri (Jurnal Agrifoodtech, 2025)
Reda dragon fruit (Hylocereus polyrizhus) peel, which is often discarded as waste, contains pectin that has potential to be used in the food industry.  This review article aims to examine the effect of microwave-assisted extraction (MAE) technology on the results of pectin extraction from red dragon fruit peel. A review was conducted on four main scientific articles discussing MAE for pectin extraction from dragon fruit peel, focusing on the chemical composition aspect and the effect of MAE technology on the extraction results. MAE technology has been shown to significantly increase extraction efficiency compared to conventional methods, with parameters such as pH, extraction time, and solid-liquid ratio affecting the extraction results. One potential application of dragon fruit peel pectin is as a base material for environmentally friendly edible films with functional added value. Formulation optimization and further testing are needed to develop the application of dragon fruit peel pectin on an industrial scale.